2010
DOI: 10.1103/physreve.82.066103
|View full text |Cite
|
Sign up to set email alerts
|

Tests of nonuniversality of the stock return distributions in an emerging market

Abstract: There is convincing evidence showing that the probability distributions of stock returns in mature markets exhibit power-law tails and both the positive and negative tails conform to the inverse cubic law. It supports the possibility that the tail exponents are universal at least for mature markets in the sense that they do not depend on stock market, industry sector, and market capitalization. We investigate the distributions of intraday returns at different time scales ( Δt=1, 5, 15, and 30 min) of all the A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 76 publications
2
18
0
Order By: Relevance
“…It was observed for several financial markets (stocks, stock indexes, exchange rates, interest rates, and the nearest delivery dates of commodities), different time scales (investigations where carried on time intervals varying from minutes to months), and different time periods [7,8,6,34]. In more specific studies, several authors observed that the tail exponent remains outside the Lévy stable domain, within a range of 3 to 5, for symmetric as well as for asymmetric tails [35,36]. As also shown in [37], the estimate of the exponent can be sensitive to the time scale, and µ is lower for high-frequency data, compared to the figures obtained with weekly or monthly time series.…”
Section: Tail Exponent Term Structurementioning
confidence: 97%
“…It was observed for several financial markets (stocks, stock indexes, exchange rates, interest rates, and the nearest delivery dates of commodities), different time scales (investigations where carried on time intervals varying from minutes to months), and different time periods [7,8,6,34]. In more specific studies, several authors observed that the tail exponent remains outside the Lévy stable domain, within a range of 3 to 5, for symmetric as well as for asymmetric tails [35,36]. As also shown in [37], the estimate of the exponent can be sensitive to the time scale, and µ is lower for high-frequency data, compared to the figures obtained with weekly or monthly time series.…”
Section: Tail Exponent Term Structurementioning
confidence: 97%
“…These individual decisions taken together define very complex behaviour of the financial markets [1][2][3][4][5] and lead to such characteristics of the financial data as multifractality [6][7][8][9][10][11], long memory, nonlinear correlations [9,12,13], the leverage effect [14,15], fat tails of financial data fluctuations [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], known together as the financial stylized facts.…”
Section: Introductionmentioning
confidence: 99%
“…For the first category of financial data, the traditional research approach is to employ the probability distribution functions in order to analyze statistical properties of various variables [1,2,3,4,5,6,7,8,9,10,11,12,13,14] and to employ correlation functions to study the cross correlation among different variables [15,16,17,18,19,20,21]. A power-law distribution has been found in many variables, such as price fluctuations, trading volume and the number of trades.…”
Section: Introductionmentioning
confidence: 99%